Musical focuses on honor, tradition, respect (Raton, NM Raton Range, 1996)
Article is a review of the Musical Pocahontas done by the Children's Storybook Theater of Riverside, California.
Newspaper article + Photograph of cast of the Children's Storybook Theater
Master list item #: 77
File location is in the Raton file Cabinet
Keywords: New Mexico Arts -- Sponsor; McCune Foundation -- Sponsor; Dairy Queen -- Sponsor; Raton Builders -- Sponsor; Live Performance; Art Reviews; Art Promotion; Raton, New Mexico; Shuler Theater